Coupling of Neuronal Nitric Oxide Synthase to NMDA Receptors via Postsynaptic Density-95 Depends on Estrogen and Contributes to the Central Control of Adult Female Reproduction - d'Anglemont de Tassigny, Xavier (J Neurosci, 2007)
Considerable research has been devoted to the understanding of how nitric oxide (NO) influences brain function. Few studies, however, have addressed how its production is physiologically regulated. Here, we report that protein–protein interactions between neuronal NO synthase (nNOS) and glutamate NMDA receptors via the scaffolding protein postsynaptic density-95 (PSD-95) in the hypothalamic preoptic region of adult female rats is sensitive to cyclic estrogen fluctuation. Coimmunoprecipitation experiments were used to assess the physical association between nNOS and NMDA receptor NR2B subunit in the preoptic region of the hypothalamus. We found that nNOS strongly interacts with NR2B at the onset of the preovulatory surge at proestrus (when estrogen levels are highest) compared with basal-stage diestrous rats. Consistently, estrogen treatment of gonadectomized female rats also increases nNOS/NR2B complex formation. Moreover, endogenous fluctuations in estrogen levels during the estrous cycle coincide with changes in the physical association of nNOS to PSD-95 and the magnitude of NO release in the preoptic region. Finally, temporary and local in vivo suppression of PSD-95 synthesis by using antisense oligodeoxynucleotides leads to inhibition of nNOS activity in the preoptic region and disrupted estrous cyclicity, a process requiring coordinated activation of neurons containing gonadotropin-releasing hormone (the neuropeptide controlling reproductive function). In conclusion, our findings identify a novel steroid-mediated molecular mechanism that enables the adult mammalian brain to control NO release under physiological conditions.